2008
DOI: 10.1080/10903120701710058
|View full text |Cite
|
Sign up to set email alerts
|

Patient andPhysician Perspectives on Ambulance Utilization

Abstract: Ambulance users were more likely to be more sick as determined by commonly used measures than nonusers. ED physicians almost always agreed with nonuse of ambulance transport and two-thirds of the time agreed that a patient's decision to use ambulance transport was appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…21,23 Also, patients may not have any other means of transport, 2,24 which might partially account for the higher rates of ambulance use among the elderly. [24][25][26] Finally, ambulances are often summoned by someone other than the patient, including family members, passers-by, and even medical professionals. 2,10,27 In all of these circumstances, the decision to request ambulance transport is arguably appropriate.…”
Section: Why People Callmentioning
confidence: 99%
“…21,23 Also, patients may not have any other means of transport, 2,24 which might partially account for the higher rates of ambulance use among the elderly. [24][25][26] Finally, ambulances are often summoned by someone other than the patient, including family members, passers-by, and even medical professionals. 2,10,27 In all of these circumstances, the decision to request ambulance transport is arguably appropriate.…”
Section: Why People Callmentioning
confidence: 99%
“…Reasons leading to an EMS call are widespread, from obviously perilous situations to simply misjudged harmless situations considered life-threatening [13]. Moreover, the EMS system could be misused by individuals lacking alternatives for help or by those simply seeking transportation to a hospital [14]. In addition, the actual aims and existing limitations of EMS systems are not completely understood by callers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a rising need for ambulance services as the elderly are more often transported by ambulance [7]. Kawakami and co-workers [8] reported that elderly, male, low household income and no possession of a car were all factors causing an increase in the use of ambulances in non-emergency situations.…”
Section: Discussionmentioning
confidence: 99%
“…Beillon and co-workers [9] have documented variations between less and more densely populated Swedish areas with the former having a more appropriate use. Jacob and colleagues [7] asked whether the treating physician agreed with the patient’s decision on transport method. There was agreement in 68% of ambulance transports and 92% of non-ambulance transports.…”
Section: Discussionmentioning
confidence: 99%